ANALISIS YURIDIS TERHADAP PENGATURAN ABORSI AKIBAT PEMERKOSAAN BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Charles Ckristian Harefa; Dessy Artina; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Abortion is an activity that causes the loss of a person's right to life. These activities trigger turmoil among the community there are community groups who agree and there are also groups of people who do not agree, in Indonesia the legality of abortion regulated in legislation. The rules are set forth in Law Number 36 Year 2009 on Health which contains legalized abortion procedures, legalized abortion is divided into two forms namely, abortion for medical emergencies and abortion for pregnancy due to rape. The purpose of writing this thesis is to analyze the juridical system of the implementation of abortion for pregnancy due to rape in Indonesia. This type of research can be classified as normative juridical research, because in this research the researcher directly conduct horizontal law synchronization research, this research is done by conducting juridical analysis on abortion arrangement due to rape in accordance with applicable laws and regulations. This research is by doing research in library and also mengiventarisasikan and analyze the relevant legislation and relevant with writing of this thesis. From the results of this study that the authors do can be concluded. Firstly, the need for a public understanding of the legality of abortion and the correct guidelines of abortion under Indonesian law. Both rules that do not reflect justice in the implementation of abortion for pregnancy due to rape should be reviewed by the Government of Indonesia for the protection of human rights The perfect position for a prosperous society. Keywords: Juridical-Abortion-Human Rights Analysis.